(untitled) (American Journal of Islam and Society, 1992)
Regardless of the definitions chosen, the conceptual frameworks adopted, or the analytical schemes utilized, many social analysts would agree that, even after decades of struggle for national development and modernization, the state of underdevelopment in Muslim countries has not changed significantly.’ on most of the standad measures conventionally used to make international comparisons as regards national development, Muslim countries occupy a disproportionate share of the bottom positions. While they languish there, the rest of the world thrusts forwad2 Despite the oil wealth of the Muslim world, most Muslim countties remain on the periphery of the emerging global economy and 8tp: becoming incteasingly marginalized as newly industrialized Third World countries enter the competitive international marketplace. The Muslims’ failure to transform their societies and become productive is due to their lack of knowledge, skills, and capabilities in most areas of intellectual endeavor, especially in the scientific and technical fields. More specifically, their inability to use the tools, techniques, and procedures of modem science for developmental changes is the result of deficiencies in their human resources. This paper examines the present status of human resoutces in the Muslim world and Assesses their prospects for the future direction of development and modernization. Its analysis is confined to the relationship ...